REVITALIZATION OF TRAINING AND EDUCATION TO INCREASE THE PRODUCTIVITY OF MSMES IN KWALA SEFRAGILE VILLAGE, LANGKAT - Suwarno, Suwarno; Andika, Rindi; Arifin, David; Lumbangaol, Nia Deniati (Proceeding International Seminar of Islamic Studies, 2024)
Micro, small and medium enterprises (MSMEs) are one of the important sectors in the Indonesian economy, including in villages. MSMEs have an important role in absorbing labor, increasing people's income, and reducing poverty. The development of MSMEs in rural communities can be done through various efforts, one of which is through training and education. Training and education can improve the skills and knowledge of MSME actors, so as to increase MSME productivity. This study aims to analyze the effect of revitalization of training and education on increasing the productivity of MSMEs in Kuala Sefragile village, Langkat. This research uses qualitative methods with a survey approach. The study population is the MSME community of Kuala Sefragile village. The study sample amounted to 50 people taken by simple random sampling method. The research data were collected using questionnaires. Data analysis was carried out using literature studies. The results showed that the revitalization of training and education had an effect on increasing the productivity of MSMEs in Kuala Sefragile village. This shows that revitalizing training and education can be one of the effective efforts to increase the productivity of MSMEs in rural communities.